Report on state-level training programme for farmer producer organizations in Odisha - International Food Policy Research Institute; Government of Odisha (International Food Policy Research Institute, 2025)
This report summarizes the outcomes of two-day State-Level Training Program for Farmer Producer Organizations (FPOs) for 3 batches held in Bhubaneswar, Odisha, from December 12-23, 2024. Organized by the Department of Agriculture & Farmer Empowerment (DAFE), Government of Odisha, in collaboration with the International Food Policy Research Institute (IFPRI) and the CGIAR, the program aimed to enhance the knowledge and skills of FPO functionaries across the state.